Differentiating pre- and minimally invasive from invasive adenocarcinoma using CT-features in persistent pulmonary part-solid nodules in Caucasian patients. Issue 4 (April 2015) - Cohen, Julien G.; Reymond, Emilie; Lederlin, Mathieu; Medici, Maud; Lantuejoul, Sylvie; Laurent, François; Arbib, François; Jankowski, Adrien; Moreau-Gaudry, Alexandre; Ferretti, Gilbert R.
Highlights: We analyzed CT-features of part-solid ground glass nodules in Caucasians. These CT-features were compared to pathology on full resection specimen. Several CT-features can help differentiating invasive adenocarcinoma. A solid component larger than 5 mm had 100% sensitivity for invasive adenocarcinoma. Abstract: Objective: To retrospectively investigate the diagnostic value of pre-operative CT-features between pre/minimally invasive and invasive lesions in part-solid persistent pulmonary ground glass nodules in a Caucasian population. Materials and methods: Retrospective review of two pre-operative CTs for 31 nodules in 30 patients. There were 10 adenocarcinomas in situ, 1 minimally invasive adenocarcinoma, 20 invasive adenocarcinomas. We analyzed the correlation between histopathology and the following CT-features: maximal axial diameter, maximal orthogonal axial diameter, height, density, size of solid component, air bronchogram, pleural retraction, nodule mass, disappearance rate and their evolution during follow-up. Results: In univariate analysis, invasive adenocarcinomas had a higher maximal height, density, solid component size, mass, a lower disappearance rate and presented more often with pleural retraction ( p  < 0.05). After logistic regression performed with the uncorrelated parameters using a method of selection of variables, only the size of solid component remained significant, with 100% sensitivity for invasive adenocarcinoma when larger than 5 mm. Conclusion: Preoperative CT-features can help differentiating in situ and minimally invasive adenocarcinomas from invasive adenocarcinomas in Caucasian patients. A solid component larger than 5 mm in diameter had 100% sensitivity for the diagnosis of invasive adenocarcinoma.